KAJIAN BAKTERI AMILOLITIK PENGHASIL POLI-Î²-HIDROKSIBUTIRAT (PHB) DARI PATI SAGU - , Nur Arfa Yanti, S.Si.,M.Si.; , Drs. Langkah Sembiring, M.Sc., Ph.D. ([Yogyakarta] : Universitas Gadjah Mada, 2011)
The study of amylolytic bacteria which produce poly-Î²-hydroxybutyrate (PHB) from sago starch was conducted to obtain the best indigenous amylolytic bacteria to be developed as PHB producer from sago starch at industrial scale. The amylolytic bacteria were selectively isolated using starch agar media and screened based on amylolytic activity. As many as 117 isolates amylolytic bacteria were isolated from processing sago starch area in Konawe regency, Southeast Sulawesi and 81 isolates among them were selected based on the amylolytic activity to be further tested for PHB production capacity. Screening of the amylolytic bacteria based on PHB producing capacity was done qualitatively by Sudan black staining and quantitatively by the spectrophotometric method. Results of the screening showed that 50 isolates among the 81 isolate bacteria were able to produce PHB ranged from 0,22-52,28 % (g PHB/g cell dry weight). Three isolate bacteria were selected based on amylolytic activity and PHB production capacity, namely isolate PPK5 had the highest amylolytic activity and PSA10 together with PPK6 were the most potential PHB producer. Amylase specific activity of the isolate PPK5, PSA10 and PPK6 was 5226,32